2007
DOI: 10.1175/jpo3074.1
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic Isopycnal Slope Spectra. Part II: Turbulence

Abstract: Isopycnal slope spectra were computed from thermistor data obtained using a microstructure platform towed through turbulence generated by internal tidal motions near the Hawaiian Ridge. The spectra were compared with turbulence dissipation rates that are estimated using shear probes. The turbulence subrange of isopycnal slope spectra extends to surprisingly large horizontal wavelengths (Ͼ100 m). A fourorder-of-magnitude range in turbulence dissipation rates at this site reveals that isopycnal slope spectra ϰx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 54 publications
12
90
0
Order By: Relevance
“…Average slope from the open ocean samples between 500-125 m wavelengths is −0.6 ± 0.1. This is consistent with Klymak and Moum (2007) who suggested that k −0.5 x is a good model for the internal-wave subrange at low horizontal wavenumbers. The relatively elevated spectral level at 1 km wavelength can be attributed to the Aves Ridge and variable local bathymetry.…”
Section: Weak Turbulencesupporting
confidence: 92%
See 2 more Smart Citations
“…Average slope from the open ocean samples between 500-125 m wavelengths is −0.6 ± 0.1. This is consistent with Klymak and Moum (2007) who suggested that k −0.5 x is a good model for the internal-wave subrange at low horizontal wavenumbers. The relatively elevated spectral level at 1 km wavelength can be attributed to the Aves Ridge and variable local bathymetry.…”
Section: Weak Turbulencesupporting
confidence: 92%
“…The spectral level at scales larger than 1 km suggest a background internal wave activity that might lead to weak turbulent fluxes; however, the existence of the regular structure in the staircase shows that double-diffusive fluxes must dominate. Klymak and Moum (2007) show that the turbulence subrange of isopycnal slope spectra extends to surprisingly large horizontal wavelengths (> 100 m) and can be distinguished with a k 1/3 x slope. In our data set, the slope spectra from the reflections are contaminated by noise at high wavenumbers, dominated by the peak at 50 m wavelength due to shot spacing.…”
Section: Weak Turbulencementioning
confidence: 88%
See 1 more Smart Citation
“…The existence of the spectrum (8.15) is not indisputable. A study by Klymak & Moum [148] suggests that the inertial subrange with the Corrsin-Obukhov spectrum extends to horizontal wavenumbers k h smaller than k O by some one or two orders of magnitude. Further discussion along these lines can be found in Riley & Lindborg [15].…”
Section: (D) Horizontal Spectrum Of the Potential Energymentioning
confidence: 99%
“…Recent work (Klymak and Moum 2007) has also demonstrated that turbulent mixing rates can be obtained from isopycnal slope spectra for wavenumbers out to greater than 1 /100 m. To obtain the isopycnal slope spectra, it is necessary to measure both the vertical and horizontal temperature and salinity structure with as high as possible resolution. Making these measurements from a towed sampling platform also requires steep trajectories within specific depth bands in order to resolve the necessary horizontal scales.…”
Section: Introductionmentioning
confidence: 99%